Evidence of hydrocarbon nanodrops in highly ordered stratum corneum model membranes - Paz Ramos, Adrian (J Lipid Res, 2018)
The stratum corneum (SC), the top layer of skin, dictates the rate of both water loss through the skin and absorption of exogenous molecules into the body. The crystalline organization of the lipids in the SC is believed to be a key feature associated with the very limited permeability of the skin. In this work, we characterized the organization of SC lipid models that include, as in native SC, cholesterol, a series of FFAs (saturated with C16-C24 chains), as well as a ceramide bearing an oleate chain-linked to a very long saturated acyl chain [N-melissoyl-oleoyloxy hexacosanoyl-D-erythro-sphingosine (Cer EOS)]. The latter is reported to be essential for the native SC lipid organization. Our (2)H-NMR, infrared, and Raman spectroscopy data reveal that Cer EOS leads to the formation of highly disordered liquid domains in a solid/crystalline matrix. The lipid organization imposes steric constraint on Cer EOS oleate chains in such a way that these hydrocarbon nanodroplets remain in the liquid state down to −30°C. These findings modify the structural description of the SC substantially and propose a novel role of Cer EOS, as this lipid is a strong modulator of SC solid/liquid balance.